Diesel hydrocracking catalyst and preparation method and application thereof

By using aluminum-rich ZSM-5 type zeolite and vulcanized Group VIB metal sulfide in the diesel-enhancing hydrocracking catalyst, combined with the functional adjustment components containing the Group VIII metal components, the problem of low selectivity and purity of light aromatic hydrocarbons in the diesel-enhancing hydrocracking reaction is solved, and efficient catalytic diesel chemical utilization is achieved.

CN119897149AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311396893.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

The selectivity and purity of light aromatic hydrocarbons in the diesel-induced hydrocracking reaction are relatively low, resulting in the inability to effectively utilize catalytic diesel, and the product does not meet the quality indicators of the aromatic hydrocarbon combined device.

Method used

Aluminum-rich ZSM-5 type zeolite is used as acid functional components, combined with Group VIB metal sulfide in the vulcanized state as hydrogenation functional components, and metal functional adjustment components containing Group VIII metal components are selected. Through hydrorefining and hydrocracking reactions in the series reactor, the form selection effect and non-aromatic cracking ability of the catalyst are improved.

Benefits of technology

The aromatic selectivity and purity of the diesel hydrocracking catalyst is significantly improved, and the efficient chemical utilization of catalytic diesel is achieved, and the product meets the quality index of the aromatic combined device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897149A_ABST
    Figure CN119897149A_ABST
Patent Text Reader

Abstract

The invention provides a diesel hydrocracking catalyst as well as a preparation method and application thereof. The diesel hydrocracking catalyst comprises the following components: aluminum-rich ZSM-5 zeolite, a hydrogenation functional component, an optional metal function adjusting component and a binder, wherein the silicon-aluminum molecular ratio of the aluminum-rich ZSM-5 zeolite is between 5 and 15, the average length of zeolite particles in at least one dimension is less than 20nm, and the hydrogenation functional component is a sulfurized metal component. The catalyst is used in a hydrocracking reaction for catalyzing firewood, and has the advantages of high light aromatic hydrocarbon selectivity and high purity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrocracking catalysts, and in particular relates to a diesel hydrocracking catalyst and a preparation method and application thereof. Background Art

[0002] In recent years, refining and chemical companies have experienced a massive oversupply of low-quality, aromatic-rich oil products, primarily catalytic diesel (CDI). CDI is a major product of the catalytic cracking process, with an annual national production of approximately 50 million tons. Although its boiling point is within the diesel fraction, processing it into diesel is uneconomical due to factors such as the presence of large amounts of polycyclic aromatic hydrocarbons, forcing some companies to use it as fuel oil. Hydrocracking technology is a key method for secondary processing of crude oil and for converting heavy oil to lighter oil. Due to its adaptability to feedstocks, flexible operation and product solutions, and high product quality, it has become a crucial means of producing high-quality light oil products and resolving chemical raw material sourcing issues.

[0003] In the existing process, light oil-type hydrocracking catalysts use gasoline or naphtha as target products, and there are problems such as low aromatic yield and purity, and excessively high diesel yield. Relevant research institutions have developed a technology that can catalyze diesel into high-octane gasoline blending components. For example, the technology disclosed in Chinese patent CN101724454A and Chinese patent CN102839018A, the aromatic content of the obtained heavy naphtha fraction is between 50-65%, which can be used as a high-octane gasoline blending component, and the catalyst used contains 20-75wt% of Y-type zeolite. However, due to the open pores of Y-type zeolite, it does not have the shape-selective effect of cracking non-aromatic hydrocarbons, and the resulting products C8, C9 and C 10 The aromatic content of the fraction is relatively low, and the non-aromatic content is relatively high. Since it cannot meet the indicators of reforming oil, it has obvious difficulties in entering the aromatics complex as a raw material for producing benzene and paraxylene.

[0004] The technology of producing light aromatics from catalytic diesel is gaining more and more attention in the industry. Chinese patent CN112570016A discloses a nitrogen-resistant aromatic hydrocracking catalyst, its preparation method and application. In this type of hydrocracking catalyst, mordenite and beta zeolite play a dominant cracking role, and the pore shape selectivity effect enables the selective conversion of tetralin-based hydrocarbons into light aromatics, and further cracks the alkanes and cycloalkanes in the light aromatic fraction. The aromatic purity of the obtained heavy naphtha can meet the needs of the aromatics complex. Chinese patent CN105435836A discloses a hydrocracking catalyst, its preparation and application, which uses a mixture of ZSM-5 molecular sieve and molybdenum-containing beta molecular sieve as a solid acid component, which can achieve efficient conversion of condensed ring aromatics and high yield of light aromatics.

[0005] The development of high-performance hydrocracking catalysts is crucial for maximizing the conversion of catalytic diesel into light aromatics that meet the quality requirements of aromatics complexes and produce high-quality light hydrocarbons that can serve as olefin feedstocks, directly feeding aromatics, olefins, and other chemical plants. Therefore, it is necessary to develop hydrocracking catalysts with enhanced shape selectivity and non-aromatic cracking capabilities to efficiently produce high-quality light aromatics from catalytic diesel. Summary of the Invention

[0006] The technical problem to be solved by the present invention is the low selectivity and purity of light aromatics obtained from catalytic diesel hydrocracking reactions. The present invention provides a catalytic diesel hydrocracking catalyst for use in the hydrocracking reaction of feedstock oil rich in polycyclic aromatic hydrocarbons. The catalyst exhibits high aromatics selectivity and purity, enabling efficient chemical utilization of catalytic diesel.

[0007] One of the objects of the present invention is to provide a diesel hydrocracking catalyst comprising: an aluminum-rich ZSM-5 zeolite, a hydrogenation functional component, an optional metal functional adjustment component, and a binder; wherein the aluminum-rich ZSM-5 zeolite has a silicon-aluminum molecular ratio of 5 to 15 and the average length of the zeolite particles in at least one dimension is less than 20 nm, and the hydrogenation functional component is a sulfided metal component.

[0008] According to the present invention, in the diesel hydrocracking catalyst:

[0009] In the aluminum-rich ZSM-5 zeolite, the content of framework aluminum accounts for more than 90% of the total aluminum, preferably more than 95%;

[0010] The hydrogenation functional component is selected from Group VIB metal sulfides, preferably at least one of metal molybdenum sulfide and metal tungsten sulfide; the Group VIB metal sulfide can continuously exert hydrogenation in a high sulfur atmosphere;

[0011] The metal function adjustment component is selected from at least one Group VIII metal-containing component, preferably at least one nickel-containing component and / or at least one cobalt-containing component; wherein the metal function adjustment component is present in the catalyst in the form of a metal sulfide, metal oxide, or metal element. The metal function adjustment component can enhance the hydrogenation capacity of the Group VIB metal sulfide. The Ni and Co components can be chemically combined with one or more other components of the final catalyst composition as compounds, such as sulfides or oxides, or present in the catalyst as metal elements.

[0012] The binder can be selected from catalyst binders commonly used in the prior art to provide good mechanical properties and textural properties, preferably at least one of an alumina-containing component and a silica-containing component. The alumina-containing component can specifically be pseudo-boehmite, and the silica-containing component can specifically be a composition of porous silica gel powder and ammonia-type silica sol; the binder can be incorporated into the catalyst in any suitable manner, for example, after mixing with zeolite, extruding, curing, drying and calcining, a catalyst carrier can be obtained.

[0013] According to the present invention, based on the total amount of the aluminum-rich ZSM-5 zeolite and the binder as 100 parts by weight, the ZSM-5 zeolite is 5 to 95 parts, preferably 10 to 90 parts, and more preferably 15 to 80 parts; the hydrogenation functional component is 1 to 30 parts, preferably 2 to 20 parts, and more preferably 3 to 18 parts; and the metal functional adjustment component is 0 to 10 parts, preferably 0.2 to 8 parts, and more preferably 0.5 to 6 parts.

[0014] The catalyst of the present invention may further include conventional components of catalysts in the art, such as diatomaceous earth, activated clay, etc., and the amount used may be the usual amount.

[0015] A second object of the present invention is to provide a method for preparing the above-mentioned diesel hydrocracking catalyst.

[0016] The hydrocracking catalyst of the present invention can be prepared by any method for preparing catalysts in the art without any particular limitation. For example, the preparation of the catalyst of the present invention may include the steps of shaping a catalyst carrier comprising the zeolite and loading components including the hydrogenation functional component and the optional metal functional regulating component, followed by calcination and activation to obtain a catalyst precursor, and then sulfurizing the catalyst precursor. Among them, the carrier shaping can be carried out by combining the zeolite with the binder and the like using methods commonly used in the art such as extrusion, ball rolling or oil column shaping; loading the metal-containing component can be carried out by methods commonly used in the art such as co-precipitation, co-gelation, kneading, ion exchange or impregnation of the metal compound with the catalyst carrier.

[0017] According to the present invention, the preparation method of the catalytic diesel hydrocracking catalyst comprises: loading a catalytic system comprising a hydrogenation functional component and an optional metal functional regulating component onto a carrier comprising the aluminum-rich ZSM-5 zeolite and a binder to obtain the catalytic diesel hydrocracking catalyst. Specifically, the preparation method comprises the following steps:

[0018] Step 1) mixing and shaping components including aluminum-rich ZSM-5 zeolite and a binder, and then drying and calcining to obtain a catalyst support;

[0019] Step 2) preparing a metal compound aqueous solution by adding a hydrogenation functional component precursor compound and optionally a metal functional regulating component precursor compound;

[0020] Step 3) impregnating the catalyst support obtained in step 1) into the aqueous solution of the metal compound obtained in step 2), taking out, drying, and calcining to obtain a catalyst precursor;

[0021] Step 4) sulfurizing the catalyst precursor obtained in step 3) to obtain the diesel hydrocracking catalyst.

[0022] According to the present invention, in the method for preparing the diesel hydrocracking catalyst:

[0023] The hydrogenation functional component precursor compound is selected from soluble Group VIB metal compounds, preferably at least one of soluble molybdenum compounds and soluble tungsten compounds, more preferably at least one of ammonium tungstate and ammonium molybdate;

[0024] The metal function regulating component precursor compound is selected from at least one soluble Group VIII metal compound, preferably at least one soluble nickel compound and / or at least one soluble cobalt compound, more preferably at least one of nickel nitrate, nickel sulfate, nickel halide, nickel oxalate, nickel acetate, cobalt nitrate, cobalt chloride, and cobalt oxalate.

[0025] According to the present invention, in the method for preparing the diesel hydrocracking catalyst:

[0026] In the step 1), the drying and calcining can adopt the drying process and calcining process commonly used in the art, for example, the drying temperature is 50-150° C., preferably 60-120° C.; the calcining temperature is 500-600° C., preferably 520-580° C.; the calcining time is 1-6 hours, preferably 2-5 hours;

[0027] In the step 2), the concentration of the metal compound aqueous solution is 3 to 50 wt%, preferably 5 to 40 wt%. An appropriate amount of ammonia water may be added to the metal compound aqueous solution to obtain a homogeneous solution.

[0028] In the step 3), the drying and calcining can adopt the drying process and calcining process commonly used in the art, for example, the drying temperature is 50-150° C., preferably 60-120° C.; the calcining temperature is 450-600° C., preferably 480-580° C.; the calcining time is 0.5-8 hours, preferably 1-6 hours; the impregnation can adopt the impregnation process commonly used in the art, such as equal volume impregnation;

[0029] The sulfurization in step 4) can adopt a sulfurization method commonly used in the art, for example, adding a carbon dioxide solution to complete the sulfurization. Preferably, the concentration of the carbon disulfide solution is 0.1-10wt%, preferably 0.2-8wt%; the solvent in the carbon disulfide solution is selected from an aromatic hydrocarbon solvent, preferably at least one of toluene and C8 aromatic hydrocarbons, which can prevent violent cracking reactions during the sulfurization process; the sulfurization conditions are: the sulfurization heating rate is 10-20°C / h, preferably 5-10°C / h; the sulfurization endpoint temperature is 300-370°C, preferably 320-360°C; and the endpoint temperature is maintained for 1-24h, preferably 4-18h.

[0030] According to the present invention, the aluminum-rich ZSM-5 zeolite is obtained by the following preparation method:

[0031] a) obtaining a colloid comprising a silicon source, a first aluminum source, an alkali source, a template, and a solvent;

[0032] b) pre-crystallizing and hydrothermally crystallizing the colloid obtained in step a) to obtain a slurry;

[0033] c) adding a second aluminum source to the slurry obtained in step b);

[0034] d) repeating pre-crystallization and hydrothermal crystallization to perform secondary crystallization to obtain the aluminum-rich ZSM-5 zeolite;

[0035] Optionally, the method further comprises the step e) calcining the aluminum-rich ZSM-5 zeolite once, then performing ion exchange, and then calcining it twice.

[0036] According to the present invention, in the method for preparing the aluminum-rich ZSM-5 zeolite:

[0037] The first aluminum source and the second aluminum source are the same or different, and are independently selected from at least one of sodium metaaluminate, aluminum hydroxide, and aluminum sulfate; and / or,

[0038] The alkali source includes alkali metal hydroxide and / or ammonia water; preferably, the alkali metal includes at least one of Na and K; and / or,

[0039] The silicon source is selected from at least one of silica gel, silica sol, and white carbon black; and / or,

[0040] The template agent is selected from organic amines, preferably at least one selected from tetrapropylammonium hydroxide, tetrapropylammonium bromide, and n-propylamine; and / or,

[0041] The solvent is water.

[0042] According to the present invention, in the method for preparing the aluminum-rich ZSM-5 zeolite:

[0043] In step a), the molar ratio of the silica source, the template, the alumina source, the sodium hydroxide, and the water is (20-50): (2-10): 1: (0.01-0.20): (120-500), wherein the silica source is calculated as SiO2 and the alumina source is calculated as Al2O3;

[0044] In the step a), a halide with a salt effect, such as sodium bromide or sodium chloride, may be optionally added as needed to promote the crystallization of the aluminum-rich zeolite. The amount of the metal salt added is not particularly limited and may be added in a commonly used amount according to actual needs.

[0045] The pre-crystallization conditions in step b) and step d) are independently: 50-100° C. for pre-crystallization for 3-60 h, preferably 60-95° C. for pre-crystallization for 5-30 h;

[0046] The hydrothermal crystallization conditions in step b) and step d) are independently: crystallization at 110-180° C. for 12-240 h, preferably, pre-crystallization at 120-170° C. for 24-200 h;

[0047] In the system obtained in step c), the molar ratio of the silica source, the template, the alumina source, the sodium hydroxide, and the water is (8-18): (0.5-2): 1: (0.005-0.015): (40-150), wherein the silica source is calculated as SiO2 and the alumina source is calculated as Al2O3;

[0048] After the secondary crystallization, the steps of filtering, washing and drying are further included; preferably, the drying temperature is 30 to 200°C;

[0049] The aluminum-rich ZSM-5 zeolite obtained in step e) is further subjected to ammonium ion exchange and calcination. According to the present invention, the sodium-type aluminum-rich ZSM-5 zeolite is obtained by the above-mentioned preparation method. Before preparing the catalyst support, the sodium-type aluminum-rich ZSM-5 zeolite needs to be exchanged with ammonium-type aluminum-rich ZSM-5 zeolite, and then calcined to obtain hydrogen-type aluminum-rich ZSM-5 zeolite. The exchange treatment and calcination treatment can adopt the exchange treatment process and calcination treatment process commonly used in the art. Specifically, the ion exchange includes ammonium exchange, and preferably, the ammonium exchange reagent includes at least one of ammonium nitrate, ammonium chloride, ammonium oxalate, and ammonium sulfate; the ammonium exchange is carried out at a temperature of 10 to 120° C. for 0.1 to 1000 hours; the concentration of the ammonium exchange reagent aqueous solution is 0.01 to 5 mol / L; the volume mass ratio of the ammonium exchange reagent aqueous solution to the ZSM-5 molecular sieve is 4 to 10 mL: 1 g; the number of ion exchanges is 1 to 20 times; after the ion exchange, filtering, washing, and drying are first performed, and then secondary calcination is performed;

[0050] The conditions of the primary calcination are: the primary calcination temperature is 200-980° C., and the primary calcination time is 0.1-250 h;

[0051] The conditions for the secondary calcination are as follows: the temperature of the secondary calcination is 400-650° C., and the time of the secondary calcination is 1-10 hours.

[0052] In the present invention, the aluminum-rich ZSM-5 zeolite and its preparation method can refer to patent ZL202311219634.1, and the relevant contents disclosed in the aforementioned document are introduced into the present invention as a reference.

[0053] A third object of the present invention is to provide an application of the above-mentioned catalytic diesel hydrocracking catalyst or the catalytic diesel hydrocracking catalyst prepared by the above-mentioned preparation method in the hydrocracking reaction of aromatic-rich diesel, preferably comprising the following steps: respectively loading the hydrorefining catalyst and the catalytic diesel hydrocracking catalyst into the first and second reactors of a single-stage series connection, and then adding the aromatic-rich diesel to carry out hydrorefining and hydrocracking reactions.

[0054] According to the present invention,

[0055] The aromatic content in the aromatic-rich diesel is not less than 50%;

[0056] The aromatic diesel is selected from at least one of catalytic diesel, coking diesel, and ethylene tar;

[0057] The aromatic-rich diesel has a nitrogen content of ≤50ppm and a sulfur content of ≤800ppm after hydrofining treatment; preferably, the nitrogen content is ≤20ppm and the sulfur content is ≤500ppm;

[0058] The hydrorefining can adopt the catalytic diesel hydrorefining technology known in the art, and the hydrorefining reaction conditions can adopt the reaction conditions of catalytic diesel hydrorefining known in the art; the hydrorefining catalyst can adopt any type of hydrorefining catalyst available in the art, as long as it can achieve the purpose of catalytic diesel hydrorefining; preferably, the hydrorefining reaction conditions include: reaction temperature of 280-400°C, hydrogen partial pressure of 2.0-15.0 MPa, liquid phase space velocity of 0.2-4.0 h -1 , the volume ratio of hydrogen to hydrocarbon is 500 to 4000; preferably, the reaction temperature is 300 to 380°C, the hydrogen partial pressure is 5.0 to 12.0 MPa, and the liquid phase space velocity is 0.5 to 2.0 h -1 , the volume ratio of hydrogen to hydrocarbon is 1000 to 3000;

[0059] The reaction conditions of the hydrocracking include: reaction temperature of 300-450°C, hydrogen partial pressure of 2.0-15.0 MPa, liquid phase space velocity of 0.2-4.0 h -1, the volume ratio of hydrogen to hydrocarbon is 500 to 4000; preferably, the reaction temperature is 320 to 420 ° C, the hydrogen partial pressure is 5.0 to 12.0 MPa, and the liquid phase space velocity is 0.5 to 2.0 h -1 , the volume ratio of hydrogen to hydrocarbon is 1000 to 3000;

[0060] The single-pass conversion rate of the hydrocracking reaction is greater than 80%;

[0061] In the hydrocracking reaction product, the benzene content in the C6 hydrocarbons is greater than 30%, and the toluene content in the C7 hydrocarbons is greater than 80%. The C6 hydrocarbons are a mixture of benzene and C6 non-aromatic hydrocarbons, and the C7 hydrocarbons are a mixture of toluene and C7 non-aromatic hydrocarbons.

[0062] The diesel hydrocracking catalyst provided by the present invention can be used to produce light aromatics and light hydrocarbons with chemical applications, catalyzing the conversion of low-value aromatic-rich oils such as diesel into chemical products such as aromatics and olefins. The diesel hydrocracking catalyst of the present invention utilizes ZSM-5 zeolite with a silicon-aluminum molecular ratio of 5 to 15 and zeolite particles with an average length of less than 20 nm in at least one dimension as the acidic functional component. The aluminum-rich ZSM-5 with a high framework aluminum content provides abundant Br acid centers. Because the average length in at least one dimension is less than 20 nm, tetralin-based hydrocarbons can contact the Br acid centers on the open outer surface and near the pores to initiate cracking reactions. Compared to conventional ZSM-5 catalysts, the catalyst exhibits significantly improved conversion activity and a high single-pass conversion rate. Furthermore, the ZSM-5 zeolite's ten-membered ring channels are more susceptible to shape selection and offer enhanced conversion capabilities for non-aromatic hydrocarbons. Furthermore, the use of sulfurized metal components, combined with hydrorefining and hydrocracking reactions in a single-stage tandem reactor, prevents deactivation due to sulfur loss during other reaction processes. The hydrocracking catalyst provided in the present application exhibits the characteristics of higher selectivity and higher purity for the conversion of diesel to light aromatics. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 This is the SEM image of the aluminum-rich ZSM-5 zeolite prepared in Example 1. DETAILED DESCRIPTION

[0064] The present invention will be described in detail below with reference to specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and are not to be construed as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made by those skilled in the art to the present invention based on the contents of the present invention still fall within the scope of protection of the present invention.

[0065] The test instruments and test conditions used in the examples are as follows:

[0066] 1. Determine the content of Si, Al and other elements in the test sample by ICP (inductively coupled plasma atomic emission spectrometry) and calculate SiO2 / Al2O3 (SAR). The instrument is Thermo IR IS Intrepid II XSP. The sample amount is 20-40 mg. The sample is fully dissolved in 40-80 mL of 40% hydrofluoric acid solution before testing.

[0067] 2. The composition of the hydrocracking catalyst was determined by XRF (X-ray fluorescence spectroscopy) using an S4 Explorer X-ray fluorescence spectrometer produced by Bruker, Germany.

[0068] 3. 27 The Al MAS NMR test was carried out on a VARIAN VNMRS-400WB nuclear magnetic resonance instrument with a measurement frequency of 104.18 MHz, a rotation speed of 10000 r / s, a relaxation time of 4 s, and KAl(SO4)2.12H2O as the standard. The chemical shift signal peak of ~60 ppm corresponds to framework aluminum, and the chemical shift signal peak of ~0 ppm corresponds to non-framework aluminum.

[0069] 4. SEM test: A Hitachi S-4800 cold field emission high-resolution scanning electron microscope (SEM) was used to observe the crystal morphology of ZSM-5 zeolite.

[0070] 5. The composition of the crude oil and light products was determined by gas chromatography. The chromatograph was an Agilent 7890A equipped with an FID detector and an FFAP capillary column for separation. The column was temperature programmed, starting at 90°C for 15 minutes, then increasing at a rate of 15°C / minute to 220°C and holding for 45 minutes.

[0071] The calculation basis of the main result data involved in the specific implementation of the present invention is:

[0072] 1. The formula for calculating the total conversion rate is:

[0073]

[0074] 2. The calculation formula for light aromatics selectivity is:

[0075]

[0076] 3. In the hydrocracking products, the benzene content in C6 hydrocarbons and the toluene content in C7 hydrocarbons are used as indicators of aromatic purity.

[0077] Diesel fuel raw materials and hydrotreating catalysts involved in the examples:

[0078] 1. To illustrate the effects of the present invention, the composition of raw materials is shown in Table 1.

[0079] Table 1. Composition of catalytic fuel raw materials

[0080]

[0081] 2. The hydrotreating catalyst used in the Examples and Comparative Examples of the present invention is the commercially available catalyst HT-1, which has a composition of 5.73 wt% NiO, 35.15 wt% MoO₃, 4.66% P₂O₅, and 54.46% Al₂O₃. Hydrotreating catalysts with similar compositions and performance indicators can meet the requirements of this technical solution.

[0082] 3. Other raw materials involved in the examples and comparative examples of the present invention are all commercially available products.

[0083] [Comparative Example 1]

[0084] Preparation of hydrocracking catalyst:

[0085] Hydrogen-type USY zeolite (SAR=12) was obtained from Sinopec Catalyst Company, with an average particle size of 1.7 microns. 43g of USY, 72.3g of pseudo-boehmite, and 2g of sesbania powder were uniformly mixed, 12ml of nitric acid and 90ml of water were added, and the mixture was kneaded into a mass, extruded, and cured at room temperature for 24 hours, dried at 110°C for 12 hours, and calcined at 550°C in air for 3 hours to obtain a hydrocracking catalyst support. 4.34g of nickel nitrate, 5.75g of ammonium molybdate, and 20ml of aqueous ammonia were dissolved in water to obtain a 50ml aqueous solution. 50g of the hydrocracking catalyst support was impregnated with 50ml of the solution in an equal volume impregnation manner, allowed to stand for 3 hours, dried at 110°C for 12 hours, and calcined at 500°C in air for 4 hours to obtain a hydrocracking catalyst precursor.

[0086] Catalyst Presulfidation: A cyclohexane solution containing 0.5% carbon disulfide was injected into a fixed-bed reactor containing a hydrocracking catalyst precursor. The temperature was ramped from room temperature at 10°C / h to a sulfidation endpoint temperature of 340°C, where it was maintained for 12 hours. The hydrocracking catalyst was presulfided. The composition of the hydrocracking catalyst Co after sulfidation was 2.4 wt% NiS-9.2 wt% MoS / 39.3 wt% USY (SAR=12)-49.1 wt% AlO (see Table 2).

[0087] Catalyst evaluation:

[0088] The evaluation was conducted using a series of microreactors, with the hydrotreating catalyst HT-1 loaded into the pre-reactor and the hydrocracking catalyst C0 loaded into the series post-reactor. A diesel feedstock was used, the reaction pressure was 6.5 MPa, and the hydrogen-to-oil ratio was 2400. The HT-1 hydrotreating catalyst had a LHSV of 0.8 h -1, reaction temperature 315℃; C1 hydrocracking catalyst space velocity (LHSV) 1.0h -1 , reaction temperature 375℃.

[0089] A high-pressure separator is installed at the outlet of the hydrocracking reactor. After the device has been running stably for 48 hours, the gas and liquid products are measured and analyzed for composition. The reaction products are classified into CH4, C2-C5 light hydrocarbons, C6-C 10 The total conversion rate and light aromatics selectivity of the four groups of hydrocarbons and unconverted components above 200 °C were calculated using the above formula. The data are summarized in Table 3.

[0090] The single-pass conversion rate is 58.6 wt%, the selectivity of light aromatics is 36.9%, the benzene content in the C6 hydrocarbons and the toluene content in the C7 hydrocarbons are 19.4% and 56.8% respectively.

[0091] [Comparative Example 2]

[0092] Preparation of hydrocracking catalyst:

[0093] Hydrogenated ZSM-5 zeolite (SAR=38) was obtained from Sinopec Catalyst Company, with an average particle size of 1.5 microns. 43g of hydrogenated ZSM-5 zeolite (SAR=38), 72.3g of pseudo-boehmite, and 2g of sesbania powder were uniformly mixed, added with 12ml of nitric acid and 90ml of water, kneaded into a mass, extruded, and cured at room temperature for 24 hours, dried at 110°C for 12 hours, and calcined at 550°C in air for 3 hours to obtain a hydrocracking catalyst support. 4.34g of nickel nitrate, 5.75g of ammonium molybdate, and 20ml of aqueous ammonia were dissolved in water to obtain a 50ml aqueous solution. 50g of the hydrocracking catalyst support was impregnated with 50ml of the solution in an equal volume impregnation manner, allowed to stand for 3 hours, dried at 110°C for 12 hours, and calcined at 500°C in air for 4 hours to obtain a hydrocracking catalyst precursor.

[0094] Catalyst Presulfidation: A cyclohexane solution containing 0.5% carbon disulfide was injected into a fixed-bed reactor containing a hydrocracking catalyst precursor. The temperature was raised from room temperature at 10°C / h to a sulfurization endpoint temperature of 340°C and maintained at this temperature for 12 hours to complete presulfidation of the hydrocracking catalyst. After sulfurization, the composition of hydrocracking catalyst C1 was 2.4 wt% NiS-9.2 wt% MoS2 / 39.3 wt% ZSM-5 (SAR=38)-49.1 wt% Al2O3, as shown in Table 2.

[0095] Catalyst evaluation:

[0096] The evaluation was conducted using a series of microreactors, with the hydrotreating catalyst HT-1 loaded into the pre-reactor and the hydrocracking catalyst C1 loaded into the post-reactor. A diesel feedstock was used, the reaction pressure was 6.5 MPa, and the hydrogen-to-oil ratio was 2400. The LHSV of the HT-1 hydrotreating catalyst was 0.8 h -1 , reaction temperature 315℃; C2 hydrocracking catalyst space velocity (LHSV) 1.0h -1 , reaction temperature 380℃.

[0097] A high-pressure separator is installed at the outlet of the hydrocracking reactor. After the device has been running stably for 48 hours, the gas and liquid products are measured and analyzed for composition. The reaction products are classified into CH4, C2-C5 light hydrocarbons, C6-C 10 The total conversion rate and light aromatics selectivity of the four groups of hydrocarbons and unconverted components above 200 °C were calculated using the above formula. The data are summarized in Table 3.

[0098] The single-pass conversion rate is 35.5wt%, the selectivity of light aromatics is 57.7%, the benzene content in the C6 hydrocarbons and the toluene content in the C7 hydrocarbons are 74.8% and 96.2% respectively.

[0099] [Example 1]

[0100] Preparation of aluminum-rich ZSM-5 zeolite:

[0101] First, NaOH, sodium bromide, and sodium metaaluminate were dissolved in deionized water. A template was then added, followed by 25% tetrapropylammonium hydroxide (OSDA). The molar ratio of SiO2, OSDA, Al2O3, NaOH, and deionized water was 40:5:1:3.5:200, and the molar ratio of NaOH to NaBr was 2:1. After uniform mixing, a milky white gel solution was obtained. This gel solution was then placed in a polytetrafluoroethylene-lined steel autoclave and pre-crystallized at 90°C for 6 hours. The solution was then hydrothermally crystallized in a rotary oven at 150°C and 20 rpm for 160 hours. Finally, the solution was cooled to room temperature using tap water to obtain a highly crystalline ZSM-5 slurry.

[0102] Appropriate amounts of sodium metaaluminate and solvent were directly added to the ZSM-5 slurry. The molar ratio of SiO2, OSDA, Al2O3, (NaOH and sodium bromide), and deionized water was 40:5:3.2:0.03:240. The above crystallization procedure was repeated for a second crystallization. The resulting product was filtered, washed, and dried, and then calcined at 550°C in air for 3 hours to obtain an aluminum-rich ZSM-5 molecular sieve. XRD characterization showed a pure phase with an MFI configuration. 27Al MAS NMR results show that 98wt% of the aluminum species are in a four-coordinate state. The silicon-aluminum ratio of the ZSM-5 molecular sieve obtained by ICP analysis is 13. Its SEM image is shown in Figure 1 , showing irregularly shaped particles with a particle size between 100-300 nm, and these particles are loosely agglomerated from basic particles with a particle size of less than 20 nm.

[0103] The obtained aluminum-rich ZSM-5 molecular sieve was added with 1 mol / L ammonium nitrate solution at 90°C and exchanged three times to exchange the sodium-type aluminum-rich ZSM-5 (SAR=13) with the ammonium-type aluminum-rich ZSM-5 (SAR=13), and then calcined at 550°C to obtain the hydrogen-type aluminum-rich ZSM-5 (SAR=13).

[0104] Preparation of hydrocracking catalyst:

[0105] 43g of hydrogen-form aluminum-rich ZSM-5 (SAR=13), 72.3g of pseudo-boehmite, and 2g of sesbania powder were uniformly mixed, 12ml of nitric acid and 90ml of water were added, and the mixture was kneaded into a mass, extruded, and cured at room temperature for 24 hours, dried at 110°C for 12 hours, and calcined at 550°C in air for 3 hours to obtain a hydrocracking catalyst support. 4.34g of nickel nitrate, 5.75g of ammonium molybdate, and 20ml of aqueous ammonia were dissolved in water to obtain 50ml of an aqueous solution. 50g of the hydrocracking catalyst support was impregnated with 50ml of the solution in an equal volume impregnation manner, allowed to stand for 3 hours, dried at 110°C for 12 hours, and calcined at 500°C in air for 4 hours to obtain a hydrocracking catalyst precursor.

[0106] Catalyst Presulfidation: A cyclohexane solution containing 1.0% carbon disulfide was injected into a fixed-bed reactor containing a hydrocracking catalyst precursor. The temperature was ramped from room temperature at 10°C / h to a sulfidation endpoint temperature of 360°C, where it was maintained for 12 hours. This presulfided catalyst was obtained. Catalyst C2 had the following composition, by weight: 2.4 wt% NiS-9.2 wt% MoS2 / 39.3 wt% ZSM-5 (SAR=13)-49.1 wt% Al2O3 (see Table 3).

[0107] The evaluation was conducted using a series microreactor system, with the hydrotreating catalyst HT-1 installed in the pre-reactor and the hydrocracking catalyst C2 installed in the series post-reactor. A diesel feedstock was used, the reaction pressure was 6.5 MPa, and the hydrogen-to-oil ratio was 2400. The HT-1 hydrotreating catalyst had a LHSV of 0.8 h -1 , reaction temperature 315℃; C2 hydrocracking catalyst space velocity (LHSV) 1.0h -1 , reaction temperature 380℃.

[0108] A high-pressure separator is installed at the outlet of the hydrocracking reactor. After the device has been running stably for 48 hours, the gas and liquid products are measured and analyzed for composition. The reaction products are classified into CH4, C2-C5 light hydrocarbons, C6-C 10 The total conversion rate and light aromatics selectivity of the four groups of hydrocarbons and unconverted components above 200 °C were calculated using the above formula. The data are summarized in Table 3.

[0109] The single-pass conversion rate is 81.5wt%, the selectivity of light aromatics is 51.6%, the benzene content in the C6 hydrocarbons and the toluene content in the C7 hydrocarbons are 49.3% and 90.8% respectively.

[0110] [Example 2]

[0111] Preparation of hydrocracking catalyst:

[0112] A hydrocracking catalyst support was prepared according to the method described in Example 1. 4.34 g of nickel nitrate, 8.78 g of ammonium tungstate, and 20 ml of aqueous ammonia were dissolved in water to yield 50 ml of an aqueous solution. 50 g of the hydrocracking catalyst support was impregnated with 50 ml of the solution in an equal volumetric manner, and the mixture was allowed to stand for 6 hours. The mixture was then dried at 90°C for 24 hours and calcined in air at 510°C for 3 hours to yield a hydrocracking catalyst precursor.

[0113] Catalyst Presulfidation: A cyclohexane solution containing 1.0% carbon disulfide was injected into a fixed-bed reactor containing a hydrocracking catalyst precursor. The temperature was ramped from room temperature at 10°C / h to a sulfidation endpoint temperature of 320°C, where it was maintained for 18 hours. This presulfided catalyst was obtained. Catalyst C3 had the following composition, by weight: 2.3 wt% NiS-13.6 wt% WS2 / 37.4 wt% ZSM-5 (SAR=13)-46.7 wt% Al2O3 (see Table 3).

[0114] The evaluation was conducted using a series of microreactors, with the hydrotreating catalyst HT-1 installed in the front reactor and the hydrocracking catalyst C3 installed in the series rear reactor. A diesel feedstock was used, the reaction pressure was 6.5 MPa, and the hydrogen-to-oil ratio was 2400. The HT-1 hydrotreating catalyst had a LHSV of 0.8 h -1 , reaction temperature 315℃; C2 hydrocracking catalyst space velocity (LHSV) 1.0h -1 , reaction temperature 380℃.

[0115] A high-pressure separator is installed at the outlet of the hydrocracking reactor. After the device has been running stably for 48 hours, the gas and liquid products are measured and analyzed for composition. The reaction products are classified into CH4, C2-C5 light hydrocarbons, C6-C 10 The total conversion rate and light aromatics selectivity of the four groups of hydrocarbons and unconverted components above 200 °C were calculated using the above formula. The data are summarized in Table 3.

[0116] The single-pass conversion rate is 86.7 wt%, the selectivity of light aromatics is 49.4%, the benzene content in the C6 hydrocarbons and the toluene content in the C7 hydrocarbons are 45.4% and 86.6% respectively.

[0117] [Example 3]

[0118] Preparation of aluminum-rich ZSM-5 zeolite:

[0119] First, NaOH, sodium bromide, and sodium aluminate were dissolved in deionized water. A template was then added, followed by 25% tetrapropylammonium hydroxide (OSDA). The molar ratio of SiO2, OSDA, Al2O3, (NaOH and sodium bromide), and deionized water was 25:3:1:0.02:135. After uniform mixing, a milky white gel solution was obtained. This gel solution was then placed in a polytetrafluoroethylene-lined steel autoclave and pre-crystallized at 70°C for 12 hours. The solution was then hydrothermally crystallized in a rotary oven at 165°C and 20 rpm for 36 hours. Finally, the solution was cooled to room temperature using tap water to obtain a highly crystalline ZSM-5 slurry.

[0120] Appropriate amounts of aluminum hydroxide and deionized water were directly added to the ZSM-5 slurry. The molar ratio of SiO2, OSDA, Al2O3, (NaOH and sodium bromide), and deionized water was 25:3:2.8:0.02:135. The above crystallization procedure was repeated for a second crystallization. The resulting product was filtered, washed, and dried, and then calcined at 550°C in air for 3 hours to obtain an aluminum-rich ZSM-5 molecular sieve. XRD characterization showed a pure phase with an MFI configuration. 27 Al MAS NMR results indicate that 96 wt% of the aluminum species are in a tetracoordinate state. ICP analysis of the ZSM-5 molecular sieve reveals a silicon-to-aluminum ratio of 8.6. The resulting aluminum-rich ZSM-5 molecular sieve is composed of loosely aggregated base particles with a particle size of less than 20 nm.

[0121] The obtained aluminum-rich ZSM-5 molecular sieve was added with 1 mol / L ammonium nitrate solution at 90°C and exchanged three times to convert the sodium-type aluminum-rich ZSM-5 (SAR=8.6) into ammonium-type aluminum-rich ZSM-5 (SAR=8.6), and then calcined at 550°C to obtain hydrogen-type aluminum-rich ZSM-5 (SAR=8.6).

[0122] Preparation of hydrocracking catalyst:

[0123] 60g of hydrogen-form aluminum-rich ZSM-5 (SAR = 8.6), 57g of pseudo-boehmite, and 2g of sesbania powder were uniformly mixed, 6ml of nitric acid and 85ml of water were added, and the mixture was kneaded into a mass, extruded, and cured at room temperature for 24 hours, dried at 110°C for 24 hours, and calcined at 550°C in air for 3 hours to obtain a hydrocracking catalyst support. 6.06g of cobalt nitrate, 5.75g of ammonium molybdate, 2.64g of ammonium tungstate, and 20ml of aqueous ammonia were dissolved in water to obtain 50ml of an aqueous solution. 50g of the hydrocracking catalyst support was impregnated with 50ml of the solution in an equal volume impregnation manner, allowed to stand for 3 hours, dried at 90°C for 24 hours, and calcined at 480°C in air for 6 hours to obtain a hydrocracking catalyst precursor.

[0124] Catalyst Presulfidation: A cyclohexane solution containing 1.0% carbon disulfide was injected into a fixed-bed reactor containing a hydrocracking catalyst precursor. The temperature was ramped from room temperature at 10°C / h to a sulfidation endpoint temperature of 330°C and maintained at this temperature for 12 hours to complete the presulfidation of the hydrocracking catalyst. Catalyst C4 was obtained. Its composition, by weight, was: 3.2 wt% CoS-8.8 wt% MoS2-4.1 wt% WS2 / 50.4 wt% ZSM-5 (SAR = 8.6)-33.5 wt% Al2O3 (see Table 3).

[0125] The evaluation was conducted using a series microreactor system, with the hydrotreating catalyst HT-1 installed in the pre-reactor and the hydrocracking catalyst C2 installed in the series post-reactor. A diesel feedstock was used, the reaction pressure was 6.5 MPa, and the hydrogen-to-oil ratio was 2400. The HT-1 hydrotreating catalyst had a LHSV of 0.8 h -1 , reaction temperature 315℃; C2 hydrocracking catalyst space velocity (LHSV) 1.0h -1 , reaction temperature 380℃.

[0126] A high-pressure separator is installed at the outlet of the hydrocracking reactor. After the device has been running stably for 48 hours, the gas and liquid products are measured and analyzed for composition. The reaction products are classified into CH4, C2-C5 light hydrocarbons, C6-C 10 The total conversion rate and light aromatics selectivity of the four groups of hydrocarbons and unconverted components above 200 °C were calculated using the above formula. The data are summarized in Table 3.

[0127] The single-pass conversion rate is 94.3 wt%, the selectivity of light aromatics is 52.7%, the benzene content in the C6 hydrocarbons and the toluene content in the C7 hydrocarbons are 60.5% and 95.4% respectively.

[0128] Table 2. Catalyst compositions obtained in Comparative Examples 1-2 and Examples 1-3

[0129]

[0130] Table 3. Product yields obtained in Comparative Examples 1-2 and Examples 1-3

[0131]

[0132] From the results in Table 3, it can be seen that the aluminum-rich ZSM-5 zeolite-catalyzed diesel hydrocracking catalysts with a silicon-aluminum molecular ratio of 5 to 15 used in Examples 1 to 3 of the present invention have higher single-pass conversion rates.

Claims

1. A diesel hydrocracking catalyst comprising: Aluminum-rich ZSM-5 zeolite, a hydrogenation functional component, an optional metal functional adjustment component and a binder; wherein the silicon-aluminum molecular ratio of the aluminum-rich ZSM-5 zeolite is between 5 and 15 and the average length of the zeolite particles in at least one dimension is less than 20nm, and the hydrogenation functional component is a sulfided metal component.

2. The catalyst according to claim 1, characterized in that In the aluminum-rich ZSM-5 zeolite, the content of framework aluminum accounts for 90wt% of the total aluminum, preferably more than 95wt%; and / or, The hydrogenation functional component is selected from Group VIB metal sulfides, preferably at least one of metal molybdenum sulfide and metal tungsten sulfide; and / or, The metal function regulating component is selected from at least one Group VIII metal-containing component, preferably at least one nickel-containing component and / or at least one cobalt-containing component; and / or, The binder is selected from at least one of an alumina-containing component and a silica-containing component.

3. The catalyst according to claim 1, characterized in that Based on the total amount of the aluminum-rich ZSM-5 zeolite and the binder as 100 parts by weight, the ZSM-5 zeolite is 5 to 95 parts, preferably 10 to 90 parts, and more preferably 15 to 80 parts; the hydrogenation functional component is 1 to 30 parts, preferably 2 to 20 parts, and more preferably 3 to 18 parts; the metal functional adjustment component is 0 to 10 parts, preferably 0.2 to 8 parts, and more preferably 0.5 to 6 parts.

4. A method for preparing the diesel hydrocracking catalyst according to any one of claims 1 to 3, comprising: The catalytic system including the hydrogenation functional component and the optional metal functional regulating component is loaded on a carrier including the aluminum-rich ZSM-5 zeolite and a binder to obtain the diesel hydrocracking catalyst.

5. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: Step 1) mixing and molding components including aluminum-rich ZSM-5 zeolite and a binder, and then drying and calcining to obtain a catalyst carrier; Step 2) preparing a metal compound aqueous solution by adding a hydrogenation functional component precursor compound and optionally a metal functional regulating component precursor compound; Step 3) impregnating the catalyst support obtained in step 1) into the aqueous solution of the metal compound obtained in step 2), taking out, drying, and calcining to obtain a catalyst precursor; Step 4) sulfurizing the catalyst precursor obtained in step 3) to obtain the diesel hydrocracking catalyst.

6. The preparation method according to claim 5, characterized in that: The hydrogenation functional component precursor compound is selected from soluble Group VIB metal compounds, preferably at least one of soluble molybdenum compounds and soluble tungsten compounds, more preferably at least one of ammonium tungstate and ammonium molybdate; and / or, The metal function regulating component precursor compound is selected from at least one soluble Group VIII metal compound, preferably at least one soluble nickel compound and / or at least one soluble cobalt compound, more preferably at least one of nickel nitrate, nickel sulfate, nickel halide, nickel oxalate, nickel acetate, cobalt nitrate, cobalt chloride, and cobalt oxalate.

7. The preparation method according to claim 5, characterized in that: In the step 1), the drying temperature is 50-150°C, preferably 60-120°C; the calcination temperature is 500-600°C, preferably 520-580°C; the calcination time is 1-6h, preferably 2-5h; and / or, In the step 2), the concentration of the aqueous solution of the metal compound is 3 to 50 wt%, preferably 5 to 40 wt%; and / or In the step 3), the drying temperature is 50-150°C, preferably 60-120°C; the calcination temperature is 450-600°C, preferably 480-580°C; the calcination time is 0.5-8h, preferably 1-6h; and / or, The vulcanization conditions in step 4) are as follows: the vulcanization heating rate is 10-20°C / h, preferably 5-10°C / h; the vulcanization end temperature is 300-370°C, preferably 320-360°C; the end temperature is maintained for 1-24h, preferably 4-18h.

8. The preparation method according to claim 4 or 5, characterized in that: The aluminum-rich ZSM-5 zeolite is obtained by the following preparation method: a) obtaining a colloid comprising a silicon source, a first aluminum source, an alkali source, a template agent and a solvent; b) pre-crystallizing and hydrothermally crystallizing the colloid obtained in step a) to obtain a slurry; c) adding a second aluminum source to the slurry obtained in step b); d) repeating pre-crystallization and hydrothermal crystallization to perform secondary crystallization to obtain the aluminum-rich ZSM-5 zeolite; Optionally, the method further comprises the step of e) calcining the aluminum-rich ZSM-5 zeolite once, then performing ion exchange, and then calcining it twice.

9. The preparation method according to claim 8, characterized in that: The first aluminum source and the second aluminum source are the same or different, and are independently selected from at least one of sodium aluminate, aluminum hydroxide, and aluminum sulfate; and / or, The alkali source includes alkali metal hydroxide and / or ammonia water; preferably, the alkali metal includes at least one of Na and K; and / or, The silicon source is selected from at least one of silica gel, silica sol and white carbon black; and / or, The template agent is selected from organic amines, preferably at least one selected from tetrapropylammonium hydroxide, tetrapropylammonium bromide, and n-propylamine; and / or, The solvent is water.

10. The preparation method according to claim 8, characterized in that: In the step a), the molar ratio of silicon source, template, aluminum source, alkali source and water is (20-50): (2-10): 1: (0.01-0.20): (120-500), wherein the silicon source is calculated as SiO2 and the aluminum source is calculated as Al2O3; and / or, The pre-crystallization conditions in step b) and step d) are independently: 50-100° C. for 3-60 h, preferably 60-95° C. for 5-30 h; and / or, The hydrothermal crystallization conditions in step b) and step d) are independently: crystallization at 110-180° C. for 12-240 h, preferably, pre-crystallization at 120-170° C. for 24-200 h; and / or, After the secondary crystallization, the steps of filtering, washing and drying are also included; preferably, the drying temperature is 30-200° C.; and / or, In the system obtained in step c), the molar ratio of silicon source, template, aluminum source, alkali source and water is (8-18): (0.5-2): 1: (0.005-0.015): (40-150), wherein the silicon source is calculated as SiO2 and the aluminum source is calculated as Al2O3; and / or, The ion exchange in step e) includes ammonium exchange, and preferably, the ammonium exchange reagent includes at least one of ammonium nitrate, ammonium chloride, ammonium oxalate, and ammonium sulfate; and / or, the ammonium exchange is carried out at a temperature of 10 to 120° C. for 0.1 to 1000 h; and / or, the concentration of the aqueous solution of the ammonium exchange reagent is 0.01 to 5 mol / L; and / or, the volume mass ratio of the aqueous solution of the ammonium exchange reagent to the ZSM-5 molecular sieve is 4 to 10 mL: 1 g; and / or, the number of ion exchanges is 1 to 20 times; and / or, after the ion exchange, filtering, washing and drying are first performed, and then secondary roasting is performed; and / or, The conditions of the primary calcination are: the primary calcination temperature is 200 to 980° C., the primary calcination time is 0.1 to 250 hours; and / or, The conditions of the secondary calcination are as follows: the temperature of the secondary calcination is 400-650° C., and the time of the secondary calcination is 1-10 hours.

11. Use of the diesel hydrocracking catalyst according to any one of claims 1 to 3 or the diesel hydrocracking catalyst prepared by the preparation method according to any one of claims 4 to 10 in the hydrocracking reaction of aromatics-rich diesel, preferably comprising the following steps: The hydrofining catalyst and the diesel hydrocracking catalyst are respectively loaded into the first reactor and the second reactor of the single-stage series connection, and then the aromatic-rich diesel is added to carry out hydrofining and hydrocracking reactions.

12. The use according to claim 11, characterized in that: The aromatic content of the aromatic-rich diesel is not less than 50%; and / or, The aromatic diesel is selected from at least one of catalytic diesel, coking diesel and ethylene tar; and / or, The aromatics-rich diesel has a nitrogen content of ≤50ppm and a sulfur content of ≤800ppm after hydrofining treatment; preferably, a nitrogen content of ≤20ppm and a sulfur content of ≤500ppm; and / or, The reaction conditions of the hydrofining include: reaction temperature of 280-400°C, hydrogen partial pressure of 2.0-15.0 MPa, liquid phase space velocity of 0.2-4.0 h -1 , the volume ratio of hydrogen to hydrocarbon is 500 to 4000; preferably, the reaction temperature is 300 to 380°C, the hydrogen partial pressure is 5.0 to 12.0 MPa, and the liquid phase space velocity is 0.5 to 2.0 h -1 , the volume ratio of hydrogen to hydrocarbon is 1000 to 3000; and / or, The reaction conditions of the hydrocracking include: reaction temperature of 300-450°C, hydrogen partial pressure of 2.0-15.0 MPa, liquid phase space velocity of 0.2-4.0 h -1 , the volume ratio of hydrogen to hydrocarbon is 500 to 4000; preferably, the reaction temperature is 320 to 420°C, the hydrogen partial pressure is 5.0 to 12.0 MPa, and the liquid phase space velocity is 0.5 to 2.0 h -1 , the volume ratio of hydrogen to hydrocarbon is 1000 to 3000; and / or, The single-pass conversion rate of the hydrocracking reaction is greater than 80%; and / or, In the hydrocracking reaction product, the benzene content in C6 hydrocarbons is greater than 30%, and the toluene content in C7 hydrocarbons is greater than 80%.

Citation Information

Patent Citations

  • Hydrocracking method for producing high-octane petrol

    CN101724454A

  • Hydrocracking method

    CN102839018A

  • Hydrocracking catalyst, and preparation method and application thereof

    CN105435836A

  • Anti-nitrogen aromatic hydrocarbon type hydrocracking catalyst as well as preparation method and application thereof

    CN112570016A

  • High-crystallinity aluminum-rich ZSM-5 molecular sieve as well as preparation method and application thereof

    CN119683645A

Cited By

  • Method and system for producing light aromatic hydrocarbon and olefin from diesel oil and application

    CN121226114A